A correlative study to evaluate the gestational age by sonological measurement of placental thickness in normal second and third trimester pregnancy - Pant, Sujit; Dashottar, Sunita (International Journal of Advances in Medicine, 2017)
Background: The dating of the pregnancy starts well before the fertilization has occurred because the gestational age is calculated from the first day of the last menstrual period (LMP). Accurate knowledge of the Gestational Age (GA) is the key for the good antenatal care and successful deliveries of babies. Menstrual history can be unreliable or misleading at many times. There may be fallacy in the measurement of the fetal biometric parameters in estimating the gestational age in some situation. So, there is a need of another parameter for supplementing the gestational age estimation with minimal error. The aim of the study was to evaluate the placental thickness as a parameter for estimation of gestational age and also to assess the growth pattern of placenta with advancing gestational age. Methods: A total of 110 pregnant women who selected randomly from the antenatal clinics (between the gestational ages from 14 weeks to 40 weeks) who did not have any maternal or fetal complications. The biometric parameters: Biparietal Diameter (BPD), Head Circumference (HC), Abdominal Circumference (AC), Femur Length (FL) and the Placental thickness (PT) were measured by ultrasound machine LOGIQ P5 unit with a curvilinear 3.5 MHz transducer. Mean value of the placental thickness along with the standard deviation (SD) and 95% confidence interval were calculated for each gestational age from 14 weeks to 40 weeks. Pearson’s correlation analysis and linear regression analysis was done quantifying the relationship between the gestational age in weeks and the placental thickness in millimetres. Results: The mean values of placental thickness show a perfect positive relationship (increasing trend) with gestational age and the mean value of placental thickness almost correspond to the gestational age till 35 weeks of the gestational age and fall marginally from 36 weeks. Placental thickness showed positive and significant correlation with gestational age (P-value<0.001) and Pearson’s correlation coefficient (r) of 0.990. Conclusions: Placental thickness can be an additional parameter for estimation of the gestational age as it almost corresponds with the gestational age in second and third trimesters. Also, any abnormal placental thickness for the particular gestational age should raise the suspicion of underlying fetal or maternal disease condition which can cause an increased or decreased in the placental thickness and should be addressed in time.